A NEW SITE RECORD OF STRIPED ASIAN TREEFROG (AMPHIBIA: RHACOPHORIDAE: Chirixalus trilaksonoi) FROM SUMATRA, WITH REEVALUATION OF ITS CONSERVATION STATUS - Alamsyah E.N. Herlambang; Wahyu Trilaksono; Awal Riyanto; M. Fakhri Fauzan; Amir Hamidy (BRIN Publishing (Penerbit BRIN), 2023)
Two of the six Chirixalus species currently known are distributed in Indonesia. Both species are only known to be distributed in Java, and they are Chirixalus trilaksonoi and Chirixalus pantaiselatan. During two field expeditions conducted in 2022 in Palembang, South Sumatra, we encountered several individuals exhibiting morphological similarities to C. trilaksonoi. Subsequent analysis, encompassing molecular, morphological, and bioacoustic, was undertaken to ascertain the identity of these individuals. The analyses outcomes unequivocally confirm that the specimens from Palembang are indeed C. trilaksonoi. Nevertheless, slight variations were observed between the Javanese and Sumatran populations of C. trilaksonoi. These populations exhibited a low genetic distance of 0.6% in mitochondrial DNA and displayed three polymorphic sites. Furthermore, there are slight differences in various morphological characteristics, and in advertising calls. The IUCN red-list status of this species was also evaluated, and based on the available evidence, we propose C. trilaksonoi as Vulnerable according to criteria B1ab(iii). This study stresses the importance of comprehensive taxon studies, especially in neighboring island, and in one biogeographical region.